The Application of Creative-Contextual Classical Guidance in Improving Children's English Literacy in Marginalized Communities - Farida, Farida; Sophya, Ida Vera; Wijaya, Mashadhi (IAIN Kudus, 2026)
The Application of Creative-Contextual Classical Guidance in Improving Children's English Literacy in Marginalized Communities. This study aims to explore the application of the classical guidance method to improve English language comprehension among children in the marginalized community of Argopuro. Using a descriptive qualitative approach, data collection was conducted through participant observation of the learning process and in-depth interviews with BKI Kreatif tutors and local residents to understand the learning dynamics of the subjects. Data analysis was conducted inductively through data reduction, presentation, and conclusion drawing. The results show that classical guidance is effective in improving English language skills when creatively designed through a playful learning method that suits the children's collective character. Despite limited facilities, the use of the surrounding environment as a contextual learning medium was able to maintain student focus and enthusiasm. The implications of this study emphasize that the group guidance approach in marginalized areas requires methodological flexibility and emotional involvement of tutors. Recommendations for future researchers include the need to develop learning media based on recycled materials (low-cost media) to overcome facility barriers. The government and related institutions are expected to replicate this guidance model to accelerate equitable access to non-formal education for children in socially vulnerable areas.Keywords: Classical Guidance, English, Marginalized Communities, Participant Observation, Contextual Education.